RADIOGRAPHY FOR FORENSIC ODONTOLOGY: A REVIEW - Nabilah Shafiyyah Rahmayati (Dentin, 2025)
ABSTRACT Background: Radiology is a branch of medicine that uses medical imaging technology to aid in the diagnosis and treatment of various diseases within the body. Radiography is a frequently performed supporting examination to help establish a diagnosis. Radiography in dentistry is divided into intraoral and extraoral. Radiographic techniques in dentistry are divided into two types: intraoral and extraoral techniques. Intraoral techniques involve examining teeth and surrounding tissues using radiography by placing a film inside the patient's oral cavity. Extraoral techniques involve radiography that is useful for viewing large areas of the skull and jaw by placing the film outside the oral cavity. The application of radiography with dentomaxillofacial imaging techniques, including 2-D periapical/panoramic radiography and 3-D imaging such as Cone-Beam CT (CBCT) and CT. This radiographic imaging can facilitate comparison between ante-mortem and post-mortem radiographic records in the individual identification process. Purpose: To report that radiography can contribute to forensic odontology Method: research design that will be used in this study is a literature review using the Preferred Reporting Items for Systematic Reviews. The literature search that will be used is the research results that have been obtained from previous researchers with the year of publication of the literature ranging from 2015-2025. Results: Articles included described role of radiography for forensic odontology Conclusion: Radiography plays a major role in the forensic odontology identification process.Keywords : forensic odontology, forensic science, radiography ABSTRAK Latar Belakang: Radiologi adalah cabang kedokteran yang menggunakan teknologi pencitraan medis untuk membantu dalam diagnosis dan pengobatan berbagai penyakit di dalam tubuh. Radiografi merupakan pemeriksaan penunjang yang sering dilakukan untuk membantu menegakkan suatu diagnosa. Radiografi pada kedokteran gigi dibagi menjadi intra oral dan ekstra oral. Teknik radiografi di kedokteran gigi terbagi menjadi dua jenis, yaitu teknik intraoral dan teknik ekstraoral. Teknik intraoral adalah pemeriksaan gigi beserta jaringan sekitarnya menggunakan radiografi dengan menempatkan film di dalam rongga mulut pasien. Teknik ekstraoral adalah pemeriksaan radiografi yang berguna untuk melihat area luas tengkorak kepala dan rahang dengan meletakkan film diluar rongga mulut. Penerapan radiografi dengan teknik pencitraan dentomaksilofasial yang meliputi radiografi periapikal/panoramik 2-D serta pencitraan 3-D seperti Cone-Beam CT (CBCT) dan CT. Pencitraan radiografi ini dapat memudahkan perbandingan antara rekam radiografis ante-mortem dan post-mortem dalam proses identifikasi individual Tujuan: Untuk melaporkan perean radiografi di odontologi forensik Metode: Desain penelitian yang akan digunakan dalam studi ini adalah tinjauan pustaka menggunakan langkah-langkah pelaporan dengan Tinjauan Sistematis. Penelusuran pustaka yang akan digunakan adalah hasil penelitian yang telah diperoleh dari peneliti sebelumnya dengan tahun publikasi pustaka berkisar antara 2015-2025. Hasil: Artikel yang disertakan menjelaskan peran Radiologi untuk tujuan odontologi forensik Kesimpulan: Radiografi berperan besar untuk proses identifikasi forensik odontologi. Kata kunci : forensik odontologi, ilmu forensic, radiologi